2011
DOI: 10.1016/j.placenta.2011.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin and spiramycin induce anti-inflammatory response in human trophoblastic (BeWo) cells infected by Toxoplasma gondii but are able to control infection

Abstract: Toxoplasma gondii is an important pathogen which may cause fetal infection if primary infection. Our previous studies have used human choriocarcinoma trophoblastic cells (BeWo cell line) as experimental model of T. gondii infection involving placental microenvironment. This study aimed to examine the effects of azithromycin and spiramycin against T. gondii infection in BeWo cells. Cells were treated with different concentrations of the macrolide antibiotics and analyzed first for cell viability using thiazolyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
15

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 26 publications
2
28
1
15
Order By: Relevance
“…Both azithromycin and PSA were able to reduce T. gondii proliferation at both tested concentrations (200 and 1000 μg/mL). These data are in agreement with our previous studies, where azithromycin treatment was able to control T. gondii infection in human trophoblast BeWo cells [19]. Additionally, azithromycin also showed a protective role against the ME49 strain of T. gondii in rodent C. callosus , reducing vertical transmission of the parasite [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both azithromycin and PSA were able to reduce T. gondii proliferation at both tested concentrations (200 and 1000 μg/mL). These data are in agreement with our previous studies, where azithromycin treatment was able to control T. gondii infection in human trophoblast BeWo cells [19]. Additionally, azithromycin also showed a protective role against the ME49 strain of T. gondii in rodent C. callosus , reducing vertical transmission of the parasite [18].…”
Section: Discussionsupporting
confidence: 92%
“…Given that azithromycin is considered safe during pregnancy and the fact that it may have activity against pathogens, such as Plasmodium and Toxoplasma , it has been suggested as a candidate for intermittent preventive treatment during pregnancy [7,17]. Previous studies have shown that azithromycin treatment in pregnant Calomys callosus and human trophoblast cells (lineage BeWo) was able to control T. gondii infection, suggesting that it may be an alternative drug for prevention of congenital infection [18,19]. Additionally, azithromycin has anti-inflammatory properties through modulating the production of proinflammatory cytokines that are produced during T. gondii infection [20].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were analyzed under BD flow cytometry (FACSCalibur; BD Company, San Diego, CA), and data were recorded using specialized BD Cell Quest software and CBA software. The results were expressed as mean fluorescence intensity (MFI) [17,19,41].…”
Section: Barbosa Et Almentioning
confidence: 99%
“…On the other hand, a normal pregnancy is characterized by a preferential Th2-type immune response and T regulatory cell responses [11], with the production of anti-inflammatory cytokines such as interleukin 10 (IL10) and transforming growth factor beta1 (TGFB1) by both maternal and fetal cells, including trophoblast cells [12,13]. The role of trophoblast cells in the immunology of pregnancy, especially in the presence of intracellular pathogens such as T. gondii and Neospora caninum, has been studied by our group using wellestablished cell lines, such as BeWo cells [14][15][16][17][18][19]. These cells were isolated from a human choriocarcinoma [20] and preserved their trophoblastic characteristics, such as hormone production and cytokine release under in vitro stimulation [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation